Adiposity, body composition and ventricular–arterial stiffness in the elderly: the Atherosclerosis Risk in Communities Study. (16th April 2018) - Fernandes‐Silva, Miguel M.; Shah, Amil M.; Claggett, Brian; Cheng, Susan; Tanaka, Hirofumi; Silvestre, Odilson M.; Nadruz, Wilson; Borlaug, Barry A.; Solomon, Scott D.
Abstract : Aim: Weight gain appears to accelerate age‐related ventricular–arterial stiffening, which has been implicated in the development of heart failure (HF), but it is unclear whether body fat accumulation underpins this association. We evaluated the relationship of adiposity, using measures of body composition, with ventricular–arterial stiffness among the elderly in the community. Methods and results: Adiposity was accessed through body mass index (BMI), waist circumference, and body fat percentage. We studied the association of these measures with carotid–femoral pulse wave velocity (cfPWV), arterial elastance index (EaI), left ventricular (LV) end‐systolic elastance index (EesI) and LV end‐diastolic elastance index (EedI) in 5520 community‐based, elderly Atherosclerosis Risk in Communities (ARIC) Study participants, who underwent echocardiography between 2011 and 2013. BMI and waist circumference were directly associated with EaI, EedI and EesI even after adjusting for age, sex, race, hypertension, diabetes mellitus, heart rate, prevalent coronary heart disease and HF. After further adjustment for BMI, body fat percentage demonstrated significant independent linear relationships with EaI [standardized beta coefficient (β)=0.17, P <0.001], EesI (β=0.08, P =0.003) and EedI (β=0.20, P <0.001), and significant non‐linear relationships with cfPWV ( P =0.033). Conclusion: In this biracial community‐based cohort, increased adiposity was associated with increased ventricular–arterial stiffness among the elderly and suggests a potential mechanism by which obesity might contribute to the development of HF.